2020
DOI: 10.1016/j.jpain.2019.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Linking Nonrestorative Sleep and Activity Interference Through Pain Catastrophizing and Pain Severity: An Intraday Process Model Among Individuals With Fibromyalgia

Abstract: Nonrestorative sleep is a key diagnostic feature of the musculoskeletal pain disorder fibromyalgia and is robustly associated with poor physical functioning, including activity interference. However, the mechanisms through which nonrestorative sleep elicits activity interference among individuals with fibromyalgia at the within-person level remain unclear. The present study tested the following 3-path mediation model, using data gathered from a 21-day electronic daily diary in 220 individuals with fibromyalgia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 80 publications
0
10
0
1
Order By: Relevance
“…A catastrophic misinterpretation of pain leads to an excessive fear of pain/injury which in turn leads to the avoidance of physical activity what contributes to exacerbate pain and disability [ 9 ]. The previous associations find evidence in the fact that pain catastrophizing is one of the most widely investigated and robust psychological predictors of poor outcomes in fibromyalgia, in particular, and chronic pain in general [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A catastrophic misinterpretation of pain leads to an excessive fear of pain/injury which in turn leads to the avoidance of physical activity what contributes to exacerbate pain and disability [ 9 ]. The previous associations find evidence in the fact that pain catastrophizing is one of the most widely investigated and robust psychological predictors of poor outcomes in fibromyalgia, in particular, and chronic pain in general [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies suggest that alterations in cognitive performance may persist even when patients’ sleep problems are controlled for Dick et al (2008) . Although FM patients report a high prevalence of sleep problems ( Anderson et al, 2012 ; Andrade et al, 2020 ; Mun et al, 2020 ; TĂŒrkoğlu and Selvi, 2020 ), the neurobiological characteristics underlying these problems and their relationship to nociceptive and cognitive impairment have not yet been fully investigated ( Ceko et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Eleven original articles were found that reported results from 9 different projects (see Supplemental Table 1, available at http://links.lww.com/PAIN/B159 ). 6 , 7 , 9 , 15 , 19 , 28 , 38 , 42 , 49 , 55 All the studies were observational designs and most investigated pain intensity, 9 , 15 , 19 , 28 , 34 , 38 , 42 , 49 , 55 pain interference, 7 , 19 , 27 and pain behavior, 19 or examined relationships between pain and other domains (such as sleep 55 or social support 9 ). One study took a more methodological approach investigating the feasibility of promising statistical models.…”
Section: Recent Pain Ecological Momentary Assessment Studiesmentioning
confidence: 99%
“…This “within-couples” design allowed the authors to show that increases in pain catastrophizing of patients were positively associated with spouse reports of patient pain behavior in concurrent and lagged analyses. In lagged analyses, Mun 34 used a structural equation modeling framework to investigate whether morning pain catastrophizing and afternoon pain severity sequentially mediated the relationship between previous night nonrestorative sleep and end-of-day activity interference. It should be clear that addressing questions like these would not be possible without repeated, momentary assessment data.…”
Section: Recent Pain Ecological Momentary Assessment Studiesmentioning
confidence: 99%